Religion, revolution, and English radicalism nonconformity in eighteenth-century politics and society - Bradley, James E. 1944- (Cambridge University Press, 1990)
In the age of the American Revolution, the political issues surrounding John Wilkes, the colonies, and parliamentary reform agitated the nation, and recent studies of party ideology and voting behavior have shown how these national issues divided England. But subsequent work on the peerage and Anglican political theory has depicted a more placid, deferential populace. This book engages the discussion by drawing attention to the social and political activities of the English Dissenters. The Nonconformists' legal standing, social status, and political behavior help illumine a number of unexamined causes for both the social stability and the political stresses of Hanoverian England. Legal inequities provoked strong opposition to the government's American policy from the dissenting elite, and while the ministers' publications suggest the depth of popular discontent, previous accounts have been unable to show how popular sentiment was transformed into radical behavior. By comparing sermons, political pamphlets, and election ephemera to poll books, city directories, and baptismal registers, this book offers an integrated approach to the study of ideology and behavior